Air electrode / separator assembly and metal-air secondary battery
Patent Information
- Application Number
- JP2023510218
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-30
- Filing Date
- 2021-11-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-11-25
Smart Images

Figure 0007639120000001 
Figure 0007639120000002 
Figure 0007639120000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an air electrode / separator assembly and a metal-air secondary battery. [Background technology]
[0002] One of the candidates for innovative batteries is the metal-air secondary battery. Because oxygen, the positive electrode active material, is supplied from the air in metal-air secondary batteries, the space inside the battery container can be maximized for filling with the negative electrode active material, which in principle makes it possible to achieve a high energy density. For example, in zinc-air secondary batteries, which use zinc as the negative electrode active material, an alkaline aqueous solution of potassium hydroxide or the like is used as the electrolyte, and a separator (partition) is used to prevent short circuits between the positive and negative electrodes. During discharge, O2 is reduced on the air electrode (positive electrode) side to form OH, as shown in the following reaction formula: - is produced, while zinc is oxidized at the negative electrode to produce ZnO. Positive electrode: O2+2H2O+4e - →4OH - Negative electrode: 2Zn+4OH - →2ZnO+2H2O+4e -
[0003] Incidentally, it is known that in zinc secondary batteries such as zinc-air secondary batteries and nickel-zinc secondary batteries, metallic zinc precipitates in the form of dendrites from the negative electrode during charging, penetrates the voids of the separator such as nonwoven fabric, and reaches the positive electrode, resulting in a short circuit. Such a short circuit caused by zinc dendrites shortens the repeated charge / discharge life. In addition, in zinc-air secondary batteries, there is also a problem that carbon dioxide in the air passes through the air electrode and dissolves in the electrolyte, precipitating alkaline carbonates and reducing the battery performance. The same problem can also occur in lithium-air secondary batteries.
[0004] In order to address the above problems, a battery has been proposed that includes a layered double hydroxide (LDH) separator that selectively allows hydroxide ions to pass through while preventing the penetration of zinc dendrites. For example, Patent Document 1 (WO 2013 / 073292) discloses that an LDH separator is provided between the air electrode and the negative electrode in a zinc-air secondary battery to prevent both short-circuiting between the positive and negative electrodes caused by zinc dendrites and the inclusion of carbon dioxide. In addition, Patent Document 2 (WO 2016 / 076047) discloses a separator structure that includes an LDH separator fitted or joined to a resin outer frame, and that the LDH separator has such high density that it is gas impermeable and / or water impermeable. This document also discloses that the LDH separator can be composited with a porous substrate. Furthermore, Patent Document 3 (WO 2016 / 067884) discloses various methods for forming an LDH dense membrane on the surface of a porous substrate to obtain a composite material (LDH separator). This method includes a step of uniformly attaching an origin substance capable of providing an origin of LDH crystal growth to a porous substrate, and subjecting the porous substrate to a hydrothermal treatment in a raw material aqueous solution to form an LDH dense membrane on the surface of the porous substrate. In addition, although it cannot be called LDH, LDH-like compounds are known as hydroxides and / or oxides having a layered crystal structure similar to LDH, and exhibit hydroxide ion conductive properties similar to LDH that can be collectively referred to as hydroxide ion conductive layered compounds. For example, Patent Document 4 (WO 2020 / 255856) discloses a hydroxide ion conductive separator comprising a porous substrate and a layered double hydroxide (LDH)-like compound that blocks the pores of the porous substrate.
[0005] In addition, in the field of metal-air secondary batteries such as zinc-air secondary batteries, an air electrode / separator assembly has been proposed in which an air electrode layer is provided on an LDH separator. Patent Document 5 (WO 2015 / 146671) discloses an air electrode / separator assembly having an air electrode layer including an air electrode catalyst, an electron conductive material, and a hydroxide ion conductive material on an LDH separator. Patent Document 6 (WO 2018 / 163353) discloses a method for producing an air electrode / separator assembly by directly bonding an air electrode layer including an LDH and carbon nanotubes (CNTs) on an LDH separator. Furthermore, Patent Document 7 (International Publication No. 2020 / 246177) discloses an air electrode / separator assembly comprising a hydroxide ion conductive separator, an interfacial layer covering one side of the separator and containing a hydroxide ion conductive material and a conductive material, and an air electrode layer provided on the interfacial layer and including an outermost catalyst layer composed of a porous collector and a layered double hydroxide (LDH) covering its surface. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2013 / 073292 [Patent Document 2] International Publication No. 2016 / 076047 [Patent Document 3] International Publication No. 2016 / 067884 [Patent Document 4] International Publication No. 2020 / 255856 [Patent Document 5] International Publication No. 2015 / 146671 [Patent Document 6] International Publication No. 2018 / 163353 [Patent Document 7] International Publication No. 2020 / 246177 Summary of the Invention
[0007] As mentioned above, metal-air secondary batteries using hydroxide ion conductive separators such as LDH separators have the excellent advantage of being able to prevent both short circuit between positive and negative electrodes caused by metal dendrites and the inclusion of carbon dioxide. In addition, the denseness of the LDH separator has the advantage of being able to suppress the evaporation of water contained in the electrolyte. However, hydroxide ion conductive separators such as LDH separators prevent the electrolyte from penetrating into the air electrode, so that no electrolyte is present in the air electrode layer. Therefore, compared with zinc-air secondary batteries using general separators (e.g., porous polymer separators) that allow the electrolyte to penetrate into the air electrode, water generated during charging is lost outside the air electrode, and water needs to be supplied from the outside during discharging, leading to a decrease in charge / discharge performance and an increase in costs. Therefore, in order to exhibit excellent charge / discharge performance while having the advantages of using hydroxide ion conductive separators such as LDH separators, an air electrode / separator assembly that can retain water generated during charging within the air electrode is desired.
[0008] The present inventors have now discovered that by constructing an air electrode / separator assembly so that it is composed of, from the top, i) a hydroxide ion conductive separator, ii) an interface layer containing a hydroxide ion conductive material and an electrically conductive material, iii) an air electrode layer containing a catalyst layer composed of a porous current collector and an LDH, and iv) a water-repellent porous layer having water repellency and air permeability, the assembly exhibits excellent charge / discharge performance when formed into a metal-air secondary battery.
[0009] Therefore, an object of the present invention is to provide an air electrode / separator assembly which, while comprising a hydroxide ion conductive separator such as an LDH separator, exhibits excellent charge / discharge performance when used in a metal-air secondary battery.
[0010] According to the present invention, the following aspects are provided. [Section 1] a hydroxide ion conducting separator; an interface layer covering one side of the hydroxide ion conductive separator and including a hydroxide ion conductive material and an electrically conductive material; an air electrode layer provided on the interface layer and including a catalyst layer made of a porous current collector and a layered double hydroxide (LDH) covering the surface of the porous current collector; a water-repellent porous layer covering the surface of the air electrode opposite to the hydroxide ion conductive separator; The cathode / separator assembly comprises: [Section 2] Item 2. The air electrode / separator assembly according to item 1, wherein the water-repellent porous material constituting the water-repellent porous layer contains a fluororesin material. [Section 3] Item 3. The air electrode / separator assembly according to item 2, wherein the fluororesin material is at least one selected from the group consisting of fully fluorinated resin, partially fluorinated resin, polyvinyl fluoride, and a fluorinated resin copolymer. [Section 4] Item 2. The air electrode / separator assembly according to item 1, wherein the water-repellent porous layer is made of a porous material coated with water-repellent fine particles. [Section 5] Item 5. The air electrode / separator assembly according to item 4, wherein the water-repellent fine particles contain a fluororesin material. [Section 6] Item 6. The air electrode / separator assembly according to item 4 or 5, wherein the porous material is at least one selected from the group consisting of a polymer material, a metal mesh, and a carbon sheet. [Section 7] The water-repellent porous layer has a thickness of 0.01 to 1 mm. 1 7. The air electrode / separator assembly according to any one of claims 1 to 6. [Section 8] The water-repellent porous layer has a porosity of 30% or more. 1 8. The air electrode / separator assembly according to any one of claims 1 to 7. [Section 9] Item 9. The air electrode / separator assembly according to any one of items 1 to 8, wherein the hydroxide ion conductive material contained in the interface layer is the same type of material as the hydroxide ion conductive material contained in the hydroxide ion conductive separator. [Section 10] Item 10. The air electrode / separator assembly according to item 9, wherein the hydroxide ion conductive material contained in the interface layer and the hydroxide ion conductive material contained in the hydroxide ion conductive separator are both LDH and / or LDH-like compounds. [Section 11] Item 11. The air electrode / separator assembly according to any one of items 1 to 10, wherein the conductive material contained in the interface layer includes a carbon material. [Section 12] Item 12. The air electrode / separator assembly according to item 11, wherein the carbon material is at least one selected from the group consisting of carbon black, graphite, carbon nanotubes, graphene, and reduced graphene oxide. [Section 13] Item 13. The air electrode / separator assembly according to any one of items 1 to 12, wherein the catalyst layer has a porosity of 60% or more. [Section 14] Item 14. The air electrode / separator assembly according to any one of items 1 to 13, wherein the LDH contained in the catalyst layer has a form of a plurality of LDH plate-like particles, and the plurality of LDH plate-like particles are bonded perpendicularly or obliquely to a surface of the porous current collector. [Section 15] Item 15. The air electrode / separator assembly according to item 14, wherein the LDH plate-like particles are connected to each other in the catalyst layer. [Section 16] Item 16. The air electrode / separator assembly according to any one of items 1 to 15, wherein the porous current collector is made of at least one material selected from the group consisting of carbon, nickel, stainless steel, and titanium. [Section 17] Item 17. The air electrode / separator assembly according to any one of items 1 to 16, wherein the porous current collector has a thickness of 0.1 to 1 mm. [Section 18] Item 18. The air electrode / separator assembly according to any one of items 1 to 17, wherein the catalyst layer contains a mixture including a hydroxide ion conductive material, a conductive material, an organic polymer, and an air electrode catalyst (however, the hydroxide ion conductive material may be the same material as the air electrode catalyst, and the conductive material may be the same material as the air electrode catalyst). [Section 19] Item 19. The air electrode / separator assembly according to any one of items 1 to 18, wherein the hydroxide ion-conductive separator is a layered double hydroxide (LDH) separator. [Section 20] Item 20. The air electrode / separator assembly according to item 19, wherein the LDH separator is composited with a porous substrate. [Section 21] 21. A battery comprising the air electrode / separator assembly according to any one of items 1 to 20, a metal negative electrode, and an electrolyte, the electrolyte being isolated from the air electrode layer via the hydroxide ion conductive separator; A metal-air secondary battery in which, from the top, the metal negative electrode, the hydroxide ion conductive separator, the air cathode layer, and the water-repellent porous layer are stacked. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view conceptually illustrating an air electrode / separator assembly according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view conceptually showing an LDH separator used in the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view conceptually showing one embodiment of plate-like particles bonded perpendicularly or obliquely to the surface of an LDH separator used in the present invention. [Figure 4A] FIG. 1 is a conceptual diagram showing an example of a He permeability measurement system used in Example A1. [Figure 4B] 4B is a schematic cross-sectional view of a sample holder and its surrounding structure used in the measurement system shown in FIG. 4A. [Diagram 5] 1 is an SEM image of the surface of the LDH separator produced in Example A1. [Figure 6A] 1 is a SEM image of the surface of carbon fibers constituting the carbon paper in the catalyst layer produced in Example B1. [Figure 6B] 6B is a magnified SEM image of the carbon fiber surface shown in FIG. 6A. [Figure 6C] 6B is an SEM image of a cross section near the surface of the carbon fiber shown in FIG. 6A. [Figure 7] 1 is a graph showing the charge / discharge characteristics measured for the evaluation cell prepared in Example B1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Air electrode / separator assembly 1 shows one embodiment of an air electrode / separator assembly using a layered double hydroxide (LDH) separator as the hydroxide ion conductive separator. In the following description, the contents of the LDH separator are also applicable to hydroxide ion conductive separators other than the LDH separator, provided that technical consistency is not impaired. In other words, in the following description, the LDH separator can be read as the hydroxide ion conductive separator, provided that technical consistency is not impaired.
[0013] The air electrode / separator assembly shown in FIG. 1 includes a layered double hydroxide (LDH) separator 12, an interface layer 14, an air electrode layer 16, and a water-repellent porous layer 19. The interface layer 14 is a layer covering one side of the LDH separator 12, and contains a hydroxide ion conductive material and an electrically conductive material. The air electrode layer 16 is a layer in contact with the interface layer 14, and is composed of a porous current collector and a catalyst layer. The water-repellent porous layer 19 is a layer covering the surface of the air electrode layer 16 opposite the LDH separator 12. By covering the air electrode layer 16 with the water-repellent porous layer 19 in this way, water generated during charging can be retained within the air electrode layer 16, and excellent charge / discharge characteristics can be exhibited without humidifying the air electrode layer 16 from the outside or blocking the passage of oxygen.
[0014] That is, as mentioned above, metal-air secondary batteries using LDH separators have the excellent advantage of being able to prevent both short circuits between the positive and negative electrodes caused by metal dendrites and the inclusion of carbon dioxide. In addition, the denseness of the LDH separator has the advantage of being able to suppress the evaporation of water contained in the electrolyte. However, since the LDH separator prevents the electrolyte from penetrating into the air electrode, no water is present in the air electrode layer, and water must be supplied from the outside during discharge. In this regard, the air electrode / separator assembly conveniently solves such problems.
[0015] Although the details of the mechanism are not entirely clear, it is believed to be as follows. That is, by covering the air electrode layer 16 with the water-repellent porous layer 19, the water generated during charging can be retained within the air electrode layer 16, and as a result, it becomes unnecessary to supply the water required during discharging from the outside. In addition, since the water-repellent porous layer 19 is porous, it provides a path for oxygen to pass through, and the water-repellent porous layer 19 can be introduced without interfering with the charge / discharge reaction.
[0016] The LDH separator 12 is defined as a separator containing layered double hydroxide (LDH) and / or an LDH-like compound (hereinafter collectively referred to as hydroxide ion conductive layered compound), and selectively passes hydroxide ions by utilizing the hydroxide ion conductivity of the hydroxide ion conductive layered compound. In this specification, the term "LDH-like compound" refers to a hydroxide and / or oxide having a layered crystal structure similar to LDH, which may not be called LDH, and can be said to be equivalent to LDH. However, in a broad sense, "LDH" can be interpreted as including not only LDH but also LDH-like compounds. Such an LDH separator can be a known one as disclosed in Patent Documents 1 to 5, and an LDH separator composited with a porous substrate is preferred. A particularly preferred LDH separator 12 is one that contains a porous substrate 12a made of a polymer material and a hydroxide ion conductive layered compound 12b that plugs the pores P of the porous substrate, as conceptually shown in FIG. 2, and this embodiment of the LDH separator 12 will be described later. By including a porous base material made of a polymer material, the battery can bend even when pressurized and is not easily broken, so that it can be housed in a battery container and pressurized in a direction in which each battery element is in close contact with each other together with other battery elements (negative electrodes, etc.). Such pressurization is particularly advantageous when a stacked battery is constructed by alternately incorporating a plurality of air electrode / separator assemblies 10 together with a plurality of metal negative electrodes in a battery container. Similarly, it is also advantageous when a battery module is constructed by housing a plurality of stacked batteries in one module container. For example, by pressurizing a zinc-air secondary battery, the gap that allows the growth of zinc dendrites between the negative electrode and the LDH separator 12 can be minimized (preferably eliminated), and thus it is expected that the extension of zinc dendrites can be more effectively prevented.
[0017] However, in the present invention, various hydroxide ion conductive separators can be used, not limited to the LDH separator 12. The hydroxide ion conductive separator is defined as a separator containing a hydroxide ion conductive material, which selectively passes hydroxide ions by utilizing the hydroxide ion conductivity of the hydroxide ion conductive material. Thus, the hydroxide ion conductive separator has gas impermeability and / or water impermeability, particularly gas impermeability. That is, the hydroxide ion conductive material constitutes all or a part of the hydroxide ion conductive separator with such high density that it exhibits gas impermeability and / or water impermeability. The definition of gas impermeability and / or water impermeability will be described later with respect to the LDH separator 12. The hydroxide ion conductive separator may be composited with a porous substrate.
[0018] The interface layer 14 includes a hydroxide ion conductive material and a conductive material. The hydroxide ion conductive material contained in the interface layer 14 has the form of a plurality of plate-like particles 13, and as conceptually shown in FIG. 3, the plurality of plate-like particles 13 are bonded perpendicularly or obliquely to the main surface of the LDH separator 12. The hydroxide ion conductive material contained in the interface layer 14 is not particularly limited as long as it has hydroxide ion conductivity and has the form of plate-like particles, but is preferably LDH and / or an LDH-like compound. In particular, when the microstructure of the surface of the LDH separator 12 produced according to a known method is observed, as shown in FIG. 3, the LDH plate-like particles 13 are typically bonded perpendicularly or obliquely to the main surface of the LDH separator 12. In the present invention, the presence of such oriented plate-like particles (hydroxide ion conductive material) and a conductive material between the LDH separator 12 and the air cathode layer 16 can significantly reduce the interface resistance. Therefore, by adopting the same type of material as the LDH and / or LDH-like compound contained in the LDH separator 12 as the hydroxide ion conductive material contained in the interface layer 14, the LDH platelet particles 13 for constituting the interface layer 14 can be prepared at the same time as the production of the LDH separator 12. On the other hand, the conductive material contained in the interface layer 14 preferably contains a carbon material. Preferable examples of the carbon material include carbon black, graphite, carbon nanotubes, graphene, reduced graphene oxide, and any combination thereof, but are not limited to these, and various other carbon materials can also be used. The interface layer 14 may be produced by applying a slurry or solution containing a carbon material (for example, a carbon ink such as graphene ink) to the surface of the LDH separator 12 where the platelet particles 13 are bonded vertically or obliquely. Alternatively, the interface layer 14 may be prepared by closely adhering the catalyst layer and the LDH separator 12 and causing the plate-like particles 13 on the surface of the LDH separator 12 to bite into the catalyst layer. In this case, the portion of the plate-like particles 13 that bites into the catalyst layer constitutes the interface layer 14.
[0019] The air electrode layer 16 is preferably composed of a porous current collector and a catalyst layer. The porous current collector is not particularly limited as long as it is composed of a conductive material having gas diffusibility, but is preferably composed of at least one selected from the group consisting of carbon, nickel, stainless steel, and titanium, and more preferably carbon. Specific examples of the porous current collector include carbon paper, nickel foam, stainless steel nonwoven fabric, and any combination thereof, and carbon paper is preferable. A commercially available porous material can be used as the current collector. The thickness of the porous current collector is preferably 0.1 to 1 mm, more preferably 0.1 to 0.5 mm, and even more preferably 0.1 to 0.3 mm, from the viewpoint of ensuring a wide reaction region, that is, a three-phase interface consisting of an ion-conducting phase (LDH), an electron-conducting phase (porous current collector), and a gas phase (air). The porosity of the catalyst layer is preferably 60% or more, more preferably 70% or more, and even more preferably 70 to 95%. In particular, in the case of carbon paper, the porosity is more preferably 60 to 90%, further preferably 70 to 90%, and particularly preferably 75 to 85%. With the above porosity, excellent gas diffusion properties can be ensured, and a wide reaction area can be ensured. In addition, since there is a large amount of pore space, clogging with generated water is unlikely to occur. The porosity can be measured by mercury intrusion porosimetry.
[0020] The catalyst layer is preferably filled with a mixture containing a hydroxide ion conducting material, a conductive material, an organic polymer, and an air electrode catalyst. The hydroxide ion conducting material may be the same material as the air electrode catalyst, and examples of such materials include LDHs containing transition metals (e.g., Ni-Fe-LDH, Co-Fe-LDH, and Ni-Fe-V-LDH). On the other hand, an example of a hydroxide ion conducting material that does not also serve as an air electrode catalyst is Mg-Al-LDH. In addition, the conductive material may be the same material as the air electrode catalyst, and examples of such materials include carbon materials, metal nanoparticles, nitrides such as TiN, LaSr3Fe3O 10 etc.
[0021] The hydroxide ion conductive material contained in the catalyst layer is not particularly limited as long as it is a material having hydroxide ion conductivity, but is preferably an LDH and / or an LDH-like compound. The composition of the LDH is not particularly limited, but is preferably a compound represented by the general formula: 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is at least one divalent cation, and M 3+ is at least one trivalent cation, and A n- is an anion with a valence of n, n is an integer of 1 or more, x is 0.1 to 0.4, and m is an arbitrary real number). 2+ can be any divalent cation, but preferred examples include Ni 2+ , Mg 2+ , Ca 2+ , Mn 2+ , Fe 2+ , Co 2+ , Cu 2+ , Zn 2+ Examples include: 3+ can be any trivalent cation, but preferred examples include Fe 3+ , V 3+ , Al 3+ , Co 3+ , Cr 3+ , In 3+ In particular, in order for LDH to have both catalytic activity and hydroxide ion conductivity, M 2+ and M 3+ Each of the transition metal ions is preferably a transition metal ion. 2+ Ni 2+ , Mn 2+ , Fe 2+ , Co 2+ , Cu 2+ and the like. Particularly preferred is Ni. 2+ On the other hand, the more preferred M 3+ is Fe 3+ , V 3+ , Co 3+ , Cr 3+and the like, and particularly preferably Fe. 3+ , V 3+ , and / or Co. 3+ In this case, M 2+ Part of the 2+ , Ca 2+ , Zn 2+ may be substituted with a metal ion other than a transition metal, such as M 3+ Part of the material is Al. 3+ , In 3+ It may be substituted with a metal ion other than a transition metal such as A. n- can be any anion, but a preferred example is NO 3- , CO3 2- , SO4 2- , O.H. - , Cl - , I - , Br - , F - More preferably, NO 3- and / or CO3 2- Therefore, the above general formula is M 2+ Ni 2+ Including M 3+ Fe 3+ Including A n- No 3- and / or CO3 2- It is preferable that the formula contains the formula: n is an integer of 1 or more, preferably 1 to 3. x is an integer of 0.1 to 0.4, preferably 0.2 to 0.35. m is an arbitrary real number. More specifically, m is a real number or integer of 0 or more, typically greater than 0 or 1 or more.
[0022] The conductive material contained in the catalyst layer is preferably at least one selected from the group consisting of conductive ceramics and carbon materials. In particular, examples of conductive ceramics include LaNiO3, LaSr3Fe3O 10 Examples of carbon materials include, but are not limited to, carbon black, graphite, carbon nanotubes, graphene, reduced graphene oxide, and any combination thereof, although various other carbon materials may also be used.
[0023] The air electrode catalyst contained in the catalyst layer is preferably at least one selected from the group consisting of LDH and other metal hydroxides, metal oxides, metal nanoparticles, and carbon materials, and more preferably at least one selected from the group consisting of LDH, metal oxides, metal nanoparticles, and carbon materials. The LDH is as described above for the hydroxide ion conductive material, and is particularly preferable in that it can function as both an air electrode catalyst and a hydroxide ion conductive material. Examples of metal hydroxides include Ni-Fe-OH, Ni-Co-OH, and any combination thereof, which may further contain a third metal element. Examples of metal oxides include Co3O4, LaNiO3, LaSr3Fe3O 10 , and any combination thereof. Examples of metal nanoparticles (typically metal particles with a particle size of 2 to 30 nm) include Pt, Ni-Fe alloy, and the like. As described above, examples of carbon materials include carbon black, graphite, carbon nanotubes, graphene, reduced graphene oxide, and any combination thereof, but are not limited thereto, and various other carbon materials can also be used. From the viewpoint of improving the catalytic performance of the carbon material, it is preferable that the carbon material further contains a metal element and / or other elements such as nitrogen, boron, phosphorus, and sulfur.
[0024] The organic polymer contained in the catalyst layer may be a known binder resin. Examples of the organic polymer include butyral resins, vinyl alcohol resins, celluloses, vinyl acetal resins, and fluorine resins, and preferably butyral resins and fluorine resins.
[0025] The catalyst layer may have a portion with low porosity in order to efficiently exchange hydroxide ions with the LDH separator 12. Specifically, the porosity of the portion with low porosity is preferably 30 to 60%, more preferably 35 to 60%, and even more preferably 40 to 55%. For the same reason, the average pore size in the portion with low porosity of the catalyst layer is preferably 5 μm or less, more preferably 0.5 to 4 μm, and even more preferably 1 to 3 μm. The porosity and average pore diameter of the catalyst layer can be measured by a) polishing the cross section of the catalyst layer with a cross-section polisher (CP), b) taking two cross-sectional images of the catalyst layer at a magnification of 10,000 times with a SEM (scanning electron microscope), c) binarizing the image using image analysis software (e.g., Image-J) based on the image data of the taken cross-sectional images, d) calculating the area of each pore for each of the two views, calculating the porosity and the pore diameter of each pore, and taking the average of these as the porosity and average pore diameter of the catalyst layer. The pore diameter can be calculated by converting the length per pixel of the image from the actual size, assuming that each pore is a perfect circle, dividing the area of each pore obtained from the image analysis by pi, and multiplying the square root by 2, and the porosity can be calculated by dividing the number of pixels corresponding to the pores by the number of pixels of the total area and multiplying by 100.
[0026] The catalyst layer can be manufactured by preparing a paste containing a hydroxide ion conductive material, a conductive material, an organic polymer, and an air electrode catalyst, and applying the paste to the surface of the LDH separator 12. The paste can be prepared by adding an organic polymer (binder resin) and an organic solvent to a mixture of the hydroxide ion conductive material, the conductive material, and the air electrode catalyst, and using a known kneading machine such as a three-roll mill. Preferred examples of the organic solvent include alcohols such as butyl carbitol and terpineol, acetate ester solvents such as butyl acetate, and N-methyl-2-pyrrolidone. The paste can be applied to the LDH separator 12 by printing. This printing can be performed by various known printing methods, but is preferably performed by screen printing.
[0027] As described above, the air electrode / separator assembly is preferably used in a metal-air secondary battery. That is, according to a preferred embodiment of the present invention, a metal-air secondary battery is provided, which comprises the air electrode / separator assembly, a metal negative electrode, and an electrolyte, and the electrolyte is separated from the air electrode layer 16 via an LDH separator 12. A zinc-air secondary battery using a zinc electrode as the metal negative electrode is particularly preferred. Alternatively, a lithium-air secondary battery using a lithium electrode as the metal negative electrode may be used.
[0028] The metal-air secondary battery preferably has a laminated structure in which the metal negative electrode, the LDH separator 12, the air electrode layer 16, and the water-repellent porous layer 19 are located in this order from the top. Therefore, this metal-air secondary battery is preferably a stationary metal-air secondary battery. A stationary metal-air secondary battery is a stationary metal-air secondary battery that is installed after a predetermined space is secured, and is distinguished from a portable metal-air secondary battery. The metal negative electrode, the LDH separator 12, the air electrode layer 16, and the water-repellent porous layer 19 are stacked vertically in a "horizontal" state. Here, "horizontal" in this specification means that the main surface of the object (i.e., the layer surface of each layer and the membrane surface of the separator) is approximately parallel to a horizontal surface. However, the terms "horizontal" and "parallel" should not be interpreted strictly, and it is acceptable for the object to have an inclination that can be recognized as horizontal or approximately parallel (to a horizontal surface) in light of common sense or social convention. Therefore, "horizontal" does not necessarily mean that the angle between the horizontal plane and the main surface is 0 degrees, i.e., perfectly parallel; the angle between the horizontal plane and the main surface may be less than 30 degrees, less than 20 degrees, less than 10 degrees, or less than 5 degrees.
[0029] Water-repellent porous layer The water-repellent porous layer 19 according to a preferred embodiment of the present invention will be described below. The water-repellent porous layer of this embodiment is required to have a predetermined air permeability, and its porosity is preferably 30% or more, more preferably 30 to 90%, even more preferably 50 to 80%, and particularly preferably 60 to 70%. The porosity may be measured in the same manner as in the measurement of the porosity of the catalyst layer described above. The thickness of the water-repellent porous layer 19 is preferably 0.01 to 1 mm, and more preferably 0.01 to 0.1 mm. Examples of the water-repellent porous material constituting the water-repellent porous layer 19 include fluororesins such as fully fluorinated resins, partially fluorinated resins, and polyvinyl fluoride.
[0030] A porous material coated with water-repellent fine particles may be used as the water-repellent porous layer 19. The porous material is not particularly limited as long as it has air permeability, but preferred examples include a resin porous sheet, a metal mesh, and a carbon sheet, and more preferably a resin porous sheet. A preferred example of the water-repellent fine particles is a fluororesin.
[0031] By covering the air electrode layer 16 with the water-repellent porous layer 19 that has water repellency and breathability, O2 necessary for the charge / discharge reaction can pass between the outside of the air electrode and the outside, and water generated during charging can be retained within the air electrode layer 16. The water remaining within the air electrode layer 16 is used for the reaction during charging. As the water reaction is completed within the air electrode layer 16 in this way, external humidification is not required.
[0032] LDH separator The LDH separator 12 according to a preferred embodiment of the present invention will be described below. Although the following description is based on a zinc-air secondary battery, the LDH separator 12 according to this embodiment can also be applied to other metal-air secondary batteries such as lithium-air secondary batteries. As described above, the LDH separator 12 according to this embodiment includes a porous substrate 12a and a hydroxide ion-conducting layered compound 12b, which is an LDH and / or an LDH-like compound, as conceptually shown in FIG. 2. In FIG. 2, the region of the hydroxide ion-conducting layered compound 12b is depicted as not being connected between the upper and lower surfaces of the LDH separator 12, but this is because it is depicted two-dimensionally as a cross section. In a three-dimensional view taking into account the depth, the region of the hydroxide ion-conducting layered compound 12b is connected between the upper and lower surfaces of the LDH separator 12, thereby ensuring the hydroxide ion conductivity of the LDH separator 12. The porous substrate 12a is made of a polymer material, and the pores of the porous substrate 12a are blocked by the hydroxide ion-conducting layered compound 12b. However, the pores of the porous substrate 12a do not need to be completely blocked, and there may be a small amount of residual pores P. By thus blocking the pores of the polymeric porous substrate 12a with the hydroxide ion-conductive layered compound 12b to highly densify it, it is possible to provide an LDH separator 12 that can more effectively suppress short circuits caused by zinc dendrites.
[0033] Furthermore, the LDH separator 12 of this embodiment not only has the desired ion conductivity required for a separator based on the hydroxide ion conductivity of the hydroxide ion conductive layered compound 12b, but also has excellent flexibility and strength. This is due to the flexibility and strength of the polymeric porous substrate 12a itself contained in the LDH separator 12. That is, the pores of the polymeric porous substrate 12a are sufficiently blocked by the hydroxide ion conductive layered compound 12b to make the LDH separator 12 dense, so that the polymeric porous substrate 12a and the hydroxide ion conductive layered compound 12b are integrated as a highly composite material, and therefore the rigidity and brittleness caused by the hydroxide ion conductive layered compound 12b, which is a ceramic material, are offset or reduced by the flexibility and strength of the polymeric porous substrate 12a.
[0034] It is desirable that the LDH separator 12 of this embodiment has very few residual pores P (pores not blocked by the hydroxide ion conductive layered compound 12b). Due to the residual pores P, the LDH separator 12 has an average porosity of, for example, 0.03% or more and less than 1.0%, preferably 0.05% or more and 0.95% or less, more preferably 0.05% or more and 0.9% or less, even more preferably 0.05 to 0.8%, and most preferably 0.05 to 0.5%. When the average porosity is within the above range, the pores of the porous substrate 12a are sufficiently blocked by the hydroxide ion conductive layered compound 12b, resulting in a very high degree of denseness, and therefore short circuits caused by zinc dendrites can be more effectively suppressed. In addition, a significantly high ion conductivity can be realized, and the LDH separator 12 can exhibit a sufficient function as a hydroxide ion conductive separator. The average porosity can be measured by a) polishing the cross section of the LDH separator with a cross-section polisher (CP), b) obtaining two cross-sectional images of the functional layer at 50,000x magnification using a FE-SEM (field emission scanning electron microscope), and c) calculating the porosity of each of the two fields of view using image inspection software (e.g., HDevelop, manufactured by MVTec Software) based on the image data of the obtained cross-sectional images, and then calculating the average value of the obtained porosities.
[0035] The LDH separator 12 is a separator containing a hydroxide ion conductive layered compound 12b, and when incorporated in a zinc secondary battery, it separates the positive electrode plate and the negative electrode plate in a manner that allows hydroxide ion conductivity. That is, the LDH separator 12 functions as a hydroxide ion conductive separator. Therefore, the LDH separator 12 has gas impermeability and / or water impermeability. Therefore, it is preferable that the LDH separator 12 is densified to have gas impermeability and / or water impermeability. In this specification, "having gas impermeability" means that, as described in Patent Documents 2 and 3, even if helium gas is brought into contact with one side of the object to be measured in water at a differential pressure of 0.5 atm, no bubbles due to helium gas are generated from the other side. In addition, in this specification, "having water impermeability" means that water that has come into contact with one side of the object to be measured does not penetrate to the other side, as described in Patent Documents 2 and 3. That is, the LDH separator 12 being gas-impermeable and / or water-impermeable means that the LDH separator 12 is dense enough to prevent gas or water from passing through, and is not a porous film or other porous material having water or gas permeability. In this way, the LDH separator 12 selectively passes only hydroxide ions due to its hydroxide ion conductivity, and can function as a battery separator. Therefore, the LDH separator 12 is extremely effective in preventing short-circuiting between the positive and negative electrodes by physically preventing the penetration of the separator by zinc dendrites generated during charging. Since the LDH separator 12 has hydroxide ion conductivity, it is possible to efficiently move hydroxide ions required between the positive and negative electrode plates, thereby realizing charge / discharge reactions in the positive and negative electrode plates.
[0036] The LDH separator 12 preferably has a He permeability per unit area of 3.0 cm / min·atm or less, more preferably 2.0 cm / min·atm or less, and even more preferably 1.0 cm / min·atm or less. A separator with a He permeability of 3.0 cm / min·atm or less can very effectively suppress the permeation of Zn (typically the permeation of zinc ions or zincate ions) in an electrolyte. In this way, the separator of this embodiment is considered in principle to be able to effectively suppress the growth of zinc dendrites when used in a zinc secondary battery by significantly suppressing Zn permeation. The He permeability is measured through a process of supplying He gas to one side of the separator to allow the He gas to permeate the separator, and a process of calculating the He permeability to evaluate the denseness of the hydroxide ion conductive separator. The He permeability is calculated by the formula F / (P×S) using the amount of He gas permeated per unit time F, the pressure difference P applied to the separator when He gas permeates, and the membrane area S through which He gas permeates. By evaluating gas permeability using He gas in this way, it is possible to evaluate the presence or absence of denseness at an extremely high level, and as a result, it is possible to effectively evaluate a high level of denseness, such as not allowing substances other than hydroxide ions (especially Zn, which causes zinc dendrite growth) to permeate as much as possible (permeating only a very small amount). This is because He gas has the smallest structural unit among the wide variety of atoms or molecules that can constitute gas, and has extremely low reactivity. In other words, He does not form molecules, and He gas is composed of He atoms alone. In this regard, hydrogen gas is composed of H2 molecules, so that He atoms alone are smaller as a gas structural unit. In the first place, H2 gas is dangerous because it is a flammable gas. And by adopting the index of He gas permeability defined by the above formula, it is possible to easily and objectively evaluate denseness regardless of various sample sizes and differences in measurement conditions. In this way, it is possible to simply, safely, and effectively evaluate whether the separator has a sufficiently high density suitable for a zinc secondary battery separator. The He permeability can be preferably measured according to the procedure shown in Evaluation 4 of the Examples described later.
[0037] In the LDH separator 12, the pores of the porous substrate 12a are filled with hydroxide ion conductive layered compounds 12b, which are LDHs and / or LDH-like compounds. As is generally known, LDHs are composed of multiple hydroxide basic layers and intermediate layers interposed between these multiple hydroxide basic layers. The hydroxide basic layers are mainly composed of metal elements (typically metal ions) and OH groups. The intermediate layers of the LDHs are composed of anions and HO. The anions are monovalent or higher anions, preferably monovalent or divalent ions. Preferably, the anions in the LDHs are OH groups. - and / or CO3 2- In addition, LDH has excellent ionic conductivity due to its inherent properties.
[0038] In general, LDH is 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an anion with a valence of n, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more. In the above basic formula, M 2+ can be any divalent cation, but preferred examples include Mg 2+ , Ca 2+ and Zn 2+ More preferably, Mg 2+ It is. 3+ can be any trivalent cation, but preferred examples include Al 3+ or Cr 3+ More preferably, Al 3+ A n- can be any anion, but preferred examples include OH - and CO3 2- Therefore, in the above basic composition formula, M 2+ Mg 2+ Including M 3+ Al 3+ Including An- OH - and / or CO3 2- It is preferable that the formula contains the formula. n is an integer of 1 or more, preferably 1 or 2. x is 0.1 to 0.4, preferably 0.2 to 0.35. m is an arbitrary number representing the number of moles of water, and is a real number of 0 or more, typically exceeding 0 or 1 or more. However, the above basic composition formula is merely a formula of a "basic composition" typically exemplified for LDH, and the constituent ions can be appropriately replaced. For example, in the above basic composition formula, M 3+ may be replaced in part or in whole by a cation having a valence of 4 or more. In that case, the anion A in the above general formula may be replaced by a cation having a valence of 4 or more. n- The coefficient x / n may be changed as appropriate.
[0039] For example, the hydroxide base layer of the LDH may contain Ni, Al, Ti, and OH groups. As described above, the intermediate layer is composed of anions and H2O. The alternately laminated structure of the hydroxide base layer and intermediate layer itself is basically the same as the alternately laminated structure of the commonly known LDH, but the LDH of this embodiment can exhibit excellent alkali resistance by forming the hydroxide base layer of the LDH with a specific element or ion including Ni, Al, Ti, and OH groups. Although the reason is not necessarily clear, it is thought that in the LDH of this embodiment, Al, which was previously thought to be easily dissolved in an alkaline solution, is difficult to dissolve in an alkaline solution due to some interaction with Ni and Ti. Nevertheless, the LDH of this embodiment can also exhibit high ionic conductivity suitable for use as a separator for an alkaline secondary battery. Ni in the LDH can take the form of nickel ions. Nickel ions in the LDH are typically Ni 2+ However, Ni 3+ The valence of the Al in the LDH can be in the form of an aluminum ion. The aluminum ion in the LDH is typically Al 3+ However, other valences are possible, so there is no particular limitation. Ti in LDH can take the form of a titanium ion. Titanium ions in LDH are typically Ti 4+Although it is considered to be so, other valences such as Ti 3+ etc. are also possible and are not particularly limited. As long as the hydroxide basic layer contains Ni, Al, Ti and OH groups, it may contain other elements or ions. However, the hydroxide basic layer preferably contains Ni, Al, Ti and OH groups as main components. That is, the hydroxide basic layer preferably consists mainly of Ni, Al, Ti and OH groups. Therefore, the hydroxide basic layer is typically composed of Ni, Al, Ti, OH groups and optionally inevitable impurities. Inevitable impurities are any elements that can inevitably be mixed in during the manufacturing process, for example, elements that can be mixed into the LDH from raw materials or substrates. As described above, since the valences of Ni, Al and Ti are not necessarily determined, it is impractical or impossible to precisely specify the LDH by a general formula. Assuming that the hydroxide basic layer is mainly composed of Ni 2+ , Al 3+ , Ti 4+ and OH groups, the corresponding LDH has the general formula: Ni 2+ 1-x-y Al 3+ x Ti 4+ y (OH)2A n- (x+2y) / n ·mH2O (wherein A n- is an n-valent anion, n is an integer of 1 or more, preferably 1 or 2, 0 < x < 1, preferably 0.01 ≦ x ≦ 0.5, 0 < y < 1, preferably 0.01 ≦ y ≦ 0.5, 0 < x + y < 1, m is 0 or more, typically a real number exceeding 0 or 1 or more) and can be represented by the basic composition. However, the above general formula should be understood as "basic composition" at most, and elements such as Ni 2+ , Al 3+ , Ti 4+ etc. should be understood as replaceable with other elements or ions (including elements or ions of other valences of the same element or elements or ions that can inevitably be mixed in during the manufacturing process) to the extent that they do not impair the basic properties of the LDH.
[0040] The LDH-like compound is a hydroxide and / or oxide having a layered crystal structure similar to LDH, although it may not be called LDH. A preferred LDH-like compound will be described later. By using an LDH-like compound, which is a hydroxide and / or oxide having a layered crystal structure having a specific composition as described later, as a hydroxide ion conductive material instead of the conventional LDH, it is possible to provide a hydroxide ion conductive separator that is excellent in alkali resistance and can more effectively suppress short circuits caused by zinc dendrites.
[0041] As described above, the LDH separator 12 includes the hydroxide ion-conducting layered compound 12b and the porous substrate 12a (typically consisting of the porous substrate 12a and the hydroxide ion-conducting layered compound 12b), and the hydroxide ion-conducting layered compound fills the pores of the porous substrate so that the LDH separator 12 exhibits hydroxide ion conductivity and gas impermeability (and therefore functions as an LDH separator exhibiting hydroxide ion conductivity). It is particularly preferred that the hydroxide ion-conducting layered compound 12b is incorporated throughout the entire thickness of the polymeric porous substrate 12a. The thickness of the LDH separator is preferably 3 to 80 μm, more preferably 3 to 60 μm, and even more preferably 3 to 40 μm.
[0042] The porous substrate 12a is made of a polymer material. The polymer porous substrate 12a has the following advantages: 1) flexibility (hence it is difficult to break even if it is thinned); 2) the porosity can be easily increased; 3) the conductivity can be easily increased (because the thickness can be reduced while increasing the porosity); and 4) it is easy to manufacture and handle. In addition, by utilizing the advantage derived from the flexibility of the above 1), it has the advantage of 5) being easy to fold or seal and bond the LDH separator including the porous substrate made of a polymer material. Preferable examples of the polymer material include polystyrene, polyethersulfone, polypropylene, epoxy resin, polyphenylene sulfide, fluororesin (tetrafluorinated resin: PTFE, etc.), cellulose, nylon, polyethylene, and any combination thereof. More preferably, from the viewpoint of a thermoplastic resin suitable for hot pressing, polystyrene, polyethersulfone, polypropylene, epoxy resin, polyphenylene sulfide, fluororesin (tetrafluorinated resin: PTFE, etc.), nylon, polyethylene, and any combination thereof. All of the above-mentioned various preferable materials have alkali resistance as resistance to the electrolyte of the battery. Particularly preferred polymeric materials are polyolefins such as polypropylene and polyethylene, which are excellent in hot water resistance, acid resistance and alkali resistance, and are low cost, and are most preferably polypropylene or polyethylene. When the porous substrate is made of a polymeric material, it is particularly preferred that the hydroxide ion-conducting layered compound is incorporated throughout the entire thickness of the porous substrate (e.g., most or almost all of the pores inside the porous substrate are filled with the hydroxide ion-conducting layered compound). As such a polymeric porous substrate, a commercially available polymeric microporous membrane can be preferably used.
[0043] The LDH separator of this embodiment can be manufactured by (i) preparing a composite material containing a hydroxide ion conductive layered compound using a polymeric porous substrate according to a known method (see, for example, Patent Documents 1 to 3), and (ii) pressing the composite material containing the hydroxide ion conductive layered compound. The pressing method may be, for example, roll pressing, uniaxial pressing, CIP (cold isostatic pressing), etc., and is not particularly limited, but roll pressing is preferred. This pressing is preferably performed while heating, since it softens the polymeric porous substrate, thereby allowing the pores of the porous substrate to be sufficiently blocked with the hydroxide ion conductive layered compound. For example, in the case of polypropylene or polyethylene, it is preferable to heat the substrate to a temperature of 60 to 200°C, which is sufficient for sufficient softening. By performing pressing such as roll pressing in such a temperature range, the average porosity derived from the residual pores of the LDH separator can be significantly reduced. As a result, the LDH separator can be extremely highly densified, and therefore short circuits caused by zinc dendrites can be more effectively suppressed. When performing roll pressing, the shape of the residual pores can be controlled by appropriately adjusting the roll gap and roll temperature, thereby making it possible to obtain an LDH separator with the desired density or average porosity.
[0044] The method for producing the hydroxide ion conductive layered compound-containing composite material (i.e., crude LDH separator) before pressing is not particularly limited, and it can be produced by appropriately modifying the conditions of the already known methods for producing LDH-containing functional layers and composite materials (i.e., LDH separators) (see, for example, Patent Documents 1 to 3). For example, (1) a porous substrate is prepared, (2) a titanium oxide sol or a mixed sol of alumina and titania is applied to the porous substrate and heat-treated to form a titanium oxide layer or an alumina-titania layer, and (3) nickel ions (Ni 2+(4) immersing the porous substrate in a raw aqueous solution containing urea and urea, and (5) hydrothermally treating the porous substrate in the raw aqueous solution to form a functional layer containing a hydroxide ion-conducting layered compound on and / or in the porous substrate, thereby producing a hydroxide ion-conducting layered compound-containing functional layer and a composite material (i.e., LDH separator). In particular, forming a titanium oxide layer or an alumina-titania layer on the porous substrate in the above step (2) not only provides the raw material for the hydroxide ion-conducting layered compound, but also functions as a starting point for the crystal growth of the hydroxide ion-conducting layered compound, thereby forming a highly densified hydroxide ion-conducting layered compound-containing functional layer uniformly without unevenness in the porous substrate. In addition, the presence of urea in the above step (3) increases the pH value by generating ammonia in the solution by utilizing the hydrolysis of urea, and the coexisting metal ions form hydroxides to obtain a hydroxide ion-conducting layered compound. In addition, since carbon dioxide is generated during the hydrolysis, a hydroxide ion-conducting layered compound in which the anion is a carbonate ion can be obtained.
[0045] In particular, when preparing a composite material (i.e., an LDH separator) in which the porous substrate is made of a polymer material and the functional layer is incorporated throughout the entire thickness of the porous substrate, it is preferable to apply the mixed sol of alumina and titania to the substrate in (2) above in such a manner that the mixed sol penetrates the entire or most of the substrate. In this way, most or almost all of the pores in the porous substrate can be filled with the hydroxide ion conductive layered compound. Examples of preferred application methods include dip coating and filtration coating, and dip coating is particularly preferred. The amount of the mixed sol attached can be adjusted by adjusting the number of applications of dip coating, etc. The substrate to which the mixed sol has been applied by dip coating, etc. may be dried and then subjected to the above steps (3) and (4).
[0046] LDH-like compounds According to a preferred embodiment of the present invention, the LDH separator may contain an LDH-like compound. The definition of the LDH-like compound is as described above. Preferred LDH-like compounds are: (a) a hydroxide and / or oxide having a layered crystal structure containing Mg and one or more elements including at least Ti selected from the group consisting of Ti, Y, and Al, or (b) a hydroxide and / or oxide having a layered crystal structure containing (i) Ti, Y, and optionally Al and / or Mg, and (ii) an additional element M which is at least one selected from the group consisting of In, Bi, Ca, Sr, and Ba; or (c) A hydroxide and / or oxide having a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In, in which the LDH-like compound is present in the form of a mixture with In(OH)3.
[0047] According to a preferred embodiment (a) of the present invention, the LDH-like compound may be a hydroxide and / or oxide having a layered crystal structure containing Mg and one or more elements including at least Ti selected from the group consisting of Ti, Y, and Al. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Mg, Ti, optionally Y, and optionally Al. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferable that the LDH-like compound does not contain Ni. For example, the LDH-like compound may further contain Zn and / or K. This can further improve the ionic conductivity of the LDH separator.
[0048] The LDH-like compound can be identified by X-ray diffraction. Specifically, when X-ray diffraction is performed on the surface of the LDH separator, a peak derived from the LDH-like compound is typically detected in the range of 5°≦2θ≦10°, more typically in the range of 7°≦2θ≦10°. As described above, LDH is a substance having an alternating laminate structure in which exchangeable anions and H2O exist as intermediate layers between stacked hydroxide basic layers. In this regard, when LDH is measured by X-ray diffraction, a peak due to the crystal structure of LDH (i.e., the (003) peak of LDH) is essentially detected at a position of 2θ=11 to 12°. In contrast, when an LDH-like compound is measured by X-ray diffraction, a peak is typically detected in the above-mentioned range shifted to the lower angle side from the above-mentioned peak position of LDH. In addition, the interlayer distance of the layered crystal structure can be determined by the Bragg formula using 2θ corresponding to the peak derived from the LDH-like compound in X-ray diffraction. The interlayer distance of the layered crystal structure constituting the LDH-like compound thus determined is typically 0.883 to 1.8 nm, and more typically 0.883 to 1.3 nm.
[0049] In the LDH separator according to the above aspect (a), the atomic ratio of Mg / (Mg+Ti+Y+Al) in the LDH-like compound determined by energy dispersive X-ray analysis (EDS) is preferably 0.03 to 0.25, more preferably 0.05 to 0.2. The atomic ratio of Ti / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0.40 to 0.97, more preferably 0.47 to 0.94. The atomic ratio of Y / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.45, more preferably 0 to 0.37. The atomic ratio of Al / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.03. Within the above ranges, the alkali resistance is more excellent, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite resistance) can be more effectively realized. Regarding LDH separators, conventionally known LDHs have the general formula: M 2+ 1-x M3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the above atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. For this reason, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH. It is preferable to perform the EDS analysis using an EDS analyzer (e.g., X-act, manufactured by Oxford Instruments) by 1) capturing an image at an accelerating voltage of 20 kV and a magnification of 5,000 times, 2) performing three-point analysis with an interval of about 5 μm in the point analysis mode, 3) repeating the above 1) and 2) once more, and 4) calculating the average value of a total of six points.
[0050] According to another preferred embodiment (b) of the present invention, the LDH-like compound may be a hydroxide and / or oxide having a layered crystal structure, comprising (i) Ti, Y, and optionally Al and / or Mg, and (ii) an additional element M. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Ti, Y, the additional element M, optionally Al, and optionally Mg. The additional element M is In, Bi, Ca, Sr, Ba, or a combination thereof. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferred that the LDH-like compound does not contain Ni.
[0051] In the LDH separator according to the above aspect (b), the atomic ratio of Ti / (Mg+Al+Ti+Y+M) in the LDH-like compound determined by energy dispersive X-ray analysis (EDS) is preferably 0.50 to 0.85, more preferably 0.56 to 0.81. The atomic ratio of Y / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.20, more preferably 0.07 to 0.15. The atomic ratio of M / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.35, more preferably 0.03 to 0.32. The atomic ratio of Mg / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.10, more preferably 0 to 0.02. The atomic ratio of Al / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.04. Within the above range, the alkali resistance is more excellent, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite resistance) can be more effectively realized. Incidentally, LDHs conventionally known as LDH separators are represented by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the above atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. For this reason, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH. It is preferable to perform the EDS analysis using an EDS analyzer (e.g., X-act, manufactured by Oxford Instruments) by 1) capturing an image at an accelerating voltage of 20 kV and a magnification of 5,000 times, 2) performing three-point analysis with an interval of about 5 μm in the point analysis mode, 3) repeating the above 1) and 2) once more, and 4) calculating the average value of a total of six points.
[0052] According to yet another preferred embodiment (c) of the present invention, the LDH-like compound is a hydroxide and / or oxide of a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In, and the LDH-like compound may be present in the form of a mixture with In(OH)3. The LDH-like compound of this embodiment is a hydroxide and / or oxide of a layered crystal structure containing Mg, Ti, Y, and optionally Al and / or In. Thus, a typical LDH-like compound is a composite hydroxide and / or composite oxide of Mg, Ti, Y, optionally Al, and optionally In. The In that may be contained in the LDH-like compound may not only be that which is intentionally added to the LDH-like compound, but may also be that which is inevitably mixed into the LDH-like compound due to the formation of In(OH)3 or the like. The above elements may be replaced with other elements or ions to the extent that the basic properties of the LDH-like compound are not impaired, but it is preferable that the LDH-like compound does not contain Ni. Incidentally, LDHs conventionally known for LDH separators are represented by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (in the formula, M 2+ is a divalent cation, M 3+ is a trivalent cation, and A n- is an n-valent anion, n is an integer of 1 or more, x is 0.1 to 0.4, and m is 0 or more). In contrast, the atomic ratio in the LDH-like compound generally deviates from the above general formula of LDH. Therefore, it can be said that the LDH-like compound in this embodiment generally has a composition ratio (atomic ratio) different from that of conventional LDH.
[0053] The mixture according to the above embodiment (c) contains not only an LDH-like compound but also In(OH)3 (typically composed of an LDH-like compound and In(OH)3). The inclusion of In(OH)3 can effectively improve the alkali resistance and dendrite resistance of the LDH separator. The content ratio of In(OH)3 in the mixture is preferably an amount that can improve the alkali resistance and dendrite resistance without substantially impairing the hydroxide ion conductivity of the LDH separator, and is not particularly limited. In(OH)3 may have a cubic crystal structure, or may have a structure in which In(OH)3 crystals are surrounded by the LDH-like compound. In(OH)3 can be identified by X-ray diffraction. EXAMPLES
[0054] The present invention will now be further illustrated by the following examples.
[0055] Example A1 The LDH separator was prepared by the following procedure and evaluated.
[0056] (1) Preparation of polymeric porous substrate A commercially available polyethylene microporous membrane with a porosity of 50%, an average pore diameter of 0.1 μm, and a thickness of 20 μm was prepared as a polymeric porous substrate, and cut to a size of 2.0 cm×2.0 cm.
[0057] (2) Alumina-titania sol coating on polymeric porous substrate A mixed sol was prepared by mixing an amorphous alumina solution (Al-ML15, Taki Chemical Co., Ltd.) and a titanium oxide sol solution (M6, Taki Chemical Co., Ltd.) so that the Ti / Al (molar ratio) was 2. The mixed sol was applied by dip coating to the substrate prepared in (1) above. The dip coating was performed by immersing the substrate in 100 ml of the mixed sol, then pulling it up vertically, and drying it in a dryer at 90°C for 5 minutes.
[0058] (3) Preparation of raw solution Nickel nitrate hexahydrate (Ni(NO3)2·6H2O, manufactured by Kanto Chemical Co., Ltd.) and urea ((NH2)2CO, manufactured by Sigma-Aldrich) were prepared as raw materials. Nickel nitrate hexahydrate was weighed out and placed in a beaker so that the concentration was 0.015 mol / L, and ion-exchanged water was added to make the total volume 75 ml. The resulting solution was stirred, and then urea / NO3 - Urea weighed out in a molar ratio of 16 was added, and the mixture was further stirred to obtain a raw material aqueous solution.
[0059] (4) Film formation by hydrothermal treatment The raw material aqueous solution and the dip-coated substrate were both sealed in a Teflon (registered trademark) sealed container (autoclave container, capacity 100 ml, outer stainless steel jacket). At this time, the substrate was fixed by floating it from the bottom of the Teflon (registered trademark) sealed container, and placed horizontally so that the solution was in contact with both sides of the substrate. Thereafter, LDH was formed on the surface and inside of the substrate by performing hydrothermal treatment at a hydrothermal temperature of 120°C for 24 hours. After a predetermined time had passed, the substrate was removed from the sealed container, washed with ion-exchanged water, and dried at 70°C for 10 hours to form LDH in the pores of the porous substrate. In this way, a composite material containing LDH was obtained.
[0060] (5) Densification by roll pressing The composite material containing the above LDH was sandwiched between a pair of PET films (Lumirror (registered trademark), manufactured by Toray Industries, Inc., thickness 40 μm) and roll pressed at a roll rotation speed of 3 mm / s, a roll temperature of 120° C., and a roll gap of 60 μm to obtain an LDH separator.
[0061] (6) Evaluation results The obtained LDH separator was evaluated as follows.
[0062] Rating 1 : Identification of LDH separator The crystalline phase of the LDH separator was measured using an X-ray diffractometer (Rigaku Corporation, RINT TTR III) under the following measurement conditions: voltage: 50 kV, current value: 300 mA, measurement range: 10 to 70° to obtain an XRD profile. The obtained XRD profile was identified using the diffraction peak of LDH (hydrotalcite compound) described in JCPDS card No. 35-0964. The LDH separator of this example was identified as LDH (hydrotalcite compound).
[0063] Rating 2 : Thickness measurement The thickness of the LDH separator was measured using a micrometer. The thickness was measured at three points, and the average value was adopted as the thickness of the LDH separator. As a result, the thickness of the LDH separator in this example was 13 μm.
[0064] Rating 3 : Average porosity measurement The cross-section of the LDH separator was polished using a cross-section polisher (CP), and two cross-sectional images of the LDH separator were obtained at a magnification of 50,000 times using a FE-SEM (ULTRA55, manufactured by Carl Zeiss). Based on this image data, the porosity of each of the two fields was calculated using image inspection software (HDevelop, manufactured by MVTec Software), and the average value was taken as the average porosity of the LDH separator. As a result, the average porosity of the LDH separator in this example was 0.8%.
[0065] Rating 4 :He transmission measurement In order to evaluate the denseness of the LDH separator from the viewpoint of He permeability, a He permeability test was carried out as follows. First, a He permeability measurement system 310 shown in Figures 4A and 4B was constructed. The He permeability measurement system 310 was configured so that He gas from a gas cylinder filled with He gas was supplied to a sample holder 316 via a pressure gauge 312 and a flow meter 314 (digital flow meter), and the He gas was permeated from one side of an LDH separator 318 held by this sample holder 316 to the other side and discharged.
[0066] The sample holder 316 has a structure including a gas supply port 316a, a sealed space 316b, and a gas exhaust port 316c, and was assembled as follows. First, an adhesive 322 was applied along the outer periphery of the LDH separator 318, and the LDH separator 318 was attached to a jig 324 (made of ABS resin) having an opening in the center. Butyl rubber packings were arranged as sealing members 326a, 326b at the upper and lower ends of the jig 324, and the sealing members 326a, 326b were sandwiched from the outside by support members 328a, 328b (made of PTFE) having openings made of flanges. In this way, the LDH separator 318, the jig 324, the sealing member 326a, and the support member 328a defined a sealed space 316b. The support members 328a, 328b were tightly fastened together by a fastening means 330 using screws so that He gas would not leak from any part other than the gas exhaust port 316c. A gas supply pipe 334 was connected via a joint 332 to a gas supply port 316 a of the sample holder 316 thus assembled.
[0067] Next, He gas was supplied to the He permeability measurement system 310 via the gas supply pipe 334, and was allowed to permeate through the LDH separator 318 held in the sample holder 316. At this time, the gas supply pressure and flow rate were monitored by the pressure gauge 312 and the flow meter 314. After the He gas permeation was carried out for 1 to 30 minutes, the He permeability was calculated. The He permeability was calculated based on the amount of He gas permeated per unit time F (cm 3 / min), the pressure difference P (atm) applied to the LDH separator when He gas permeates, and the membrane area S (cm 2 ) was used to calculate the amount of He gas permeation F (cm 3 / min) was read directly from flowmeter 314. The differential pressure P was the gauge pressure read from pressure gauge 312. He gas was supplied so that the differential pressure P was in the range of 0.05 to 0.90 atm. As a result, the He permeability per unit area of the LDH separator was 0.0 cm / min atm.
[0068] Rating 5 : Observation of the microstructure of the separator surface When the surface of the LDH separator was observed by SEM, it was found that numerous LDH plate-like particles were bonded perpendicularly or obliquely to the main surface of the LDH separator, as shown in FIG.
[0069] Examples B1 to B3 An air electrode / separator assembly having two layers, an interface layer and a catalyst layer, on the LDH separator produced in Example A1 was produced in the following manner, and was evaluated.
[0070] (1) Preparation of catalyst layer (1a) Iron oxide sol coating on conductive porous substrate 10 ml of iron oxide sol (Fe-C10, iron oxide concentration 10% by weight, manufactured by Taki Chemical Industry Co., Ltd.) diluted with ion-exchanged water to a concentration of 5% by weight was placed in a beaker, and carbon paper (TGP-H-060, manufactured by Toray, thickness 200 μm) was immersed in the sol. A vacuum was applied to the beaker, allowing the iron oxide sol to fully penetrate into the carbon paper. The carbon paper was pulled out of the beaker with tweezers and dried at 80°C for 30 minutes to obtain carbon paper with iron oxide particles attached as a substrate.
[0071] (1b) Preparation of raw solution Nickel nitrate hexahydrate (Ni(NO3)2 6H2O, manufactured by Kanto Chemical Co., Ltd.) and urea ((NH2)2CO, manufactured by Mitsui Chemicals, Inc.) were prepared as raw materials. Nickel nitrate hexahydrate was weighed out and placed in a beaker so that the concentration was 0.03 mol / L, and ion-exchanged water was added to make the total volume 75 ml. The resulting solution was stirred, and then urea was added to the solution so that the concentration was 0.96 mol / L, and further stirring was performed to obtain a raw material aqueous solution.
[0072] (1c) Film formation by hydrothermal treatment The raw material aqueous solution prepared in (1b) above and the substrate prepared in (1a) above were both sealed in a Teflon (registered trademark) sealed container (autoclave container, capacity 100 ml, outer stainless steel jacket). At this time, the substrate was fixed by floating it from the bottom of the Teflon (registered trademark) sealed container, and placed horizontally so that the solution was in contact with both sides of the substrate. Thereafter, LDH was formed on the surface of the fibers inside the substrate by performing hydrothermal treatment at a hydrothermal temperature of 120°C for 20 hours. After a predetermined time had passed, the substrate was taken out of the sealed container, washed with ion-exchanged water, and dried at 80°C for 30 minutes to obtain a catalyst layer as an air electrode layer. When the microstructure of the obtained catalyst layer was observed by SEM, the images shown in Figures 6A to 6C were obtained. Figure 6B is an enlarged image of the surface of the carbon fibers constituting the carbon paper shown in Figure 6A, and Figure 6C is an enlarged image of a cross section near the surface of the carbon fibers shown in Figure 6A. From these figures, it was observed that numerous LDH platelet particles were bound vertically or obliquely to the surface of the carbon fibers that make up the carbon paper, and that these LDH platelet particles were connected to each other.
[0073] The porosity of the resulting catalyst layer was measured by mercury intrusion porosimetry and was found to be 76%.
[0074] (2) Bonding of catalyst layer and LDH separator Carbon powder (Denka Black, manufactured by Denka Co., Ltd.) was added at 5% by weight to ethanol (Kanto Chemical Co., Ltd., purity 99.5%) and dispersed by ultrasonic waves to prepare a carbon slurry. The obtained slurry was applied by spin coating onto the LDH separator obtained in Example A1, and then a catalyst layer (air electrode layer) was placed on it. A weight was placed on the catalyst layer and dried at 80°C in air for 2 hours. In this way, an air electrode layer composed of a catalyst layer (thickness 200 μm) was formed on the LDH separator. At this time, an interface layer (thickness 0.2 μm) containing LDH plate-like particles (derived from the LDH separator) and carbon (derived from the carbon slurry) was simultaneously formed between the LDH separator and the air electrode layer. Only for Example B3, a PTFE porous film (SEF-010, manufactured by Chukoh Chemical Industry Co., Ltd.) was attached onto the catalyst layer (air electrode layer) to form a water-repellent porous layer (porosity: 65%). In this way, air electrode / separator assemblies without a water-repellent porous layer (Examples B1 and B2) and an air electrode / separator assembly with a water-repellent porous layer (Example B3) were obtained.
[0075] (3) Assembly and evaluation of evaluation cells Air electrode / separator assembly of The metal zinc plate was used as the negative electrode on the LDH separator side, and the negative electrode was stacked on top. The resulting stack was clamped in a holding jig with a sealing member tightly biting the outer periphery of the LDH separator, and firmly fixed with screws. This holding jig has an oxygen inlet on the air electrode side and a liquid injection port through which electrolyte can be introduced on the metal zinc plate side. A 5.4 M KOH aqueous solution saturated with zinc oxide was added to the negative electrode side of the assembly thus obtained to make an evaluation cell.
[0076] The charge / discharge characteristics of the evaluation cell were measured using an electrochemical measurement device (HZ-Pro S12, manufactured by Hokuto Denko Corporation) under the following conditions: Humidified air electrode gas: Water vapor saturated (25°C) oxygen (flow rate 200cc / min) (example B1 only) Air electrode gas without humidification: Oxygen (flow rate 200cc / min) (examples B2 and B3 only) ·Charge / discharge current density: 2mA / cm 2 ·Charge / discharge time: 10 minutes charge / 10 minutes discharge The measurements were performed. The results are shown in FIG. 7. In FIG. 7, the horizontal axis indicates the number of cycles, and the vertical axis indicates the end voltage of each charge / discharge. FIG. 7 shows that in Example B2 (Comparative Example) in which a non-humidified air electrode gas was used, the discharge voltage began to drop around the sixth cycle, but in Example B3 (Example) in which the air electrode was covered with a water-repellent porous layer, a high charge / discharge voltage was shown that was almost equivalent to Example B1 (Reference Example) in which a humidified air electrode gas was used, and that a high charge / discharge efficiency can be achieved.
Claims
1. a hydroxide ion conducting separator; an interface layer covering one side of the hydroxide ion conductive separator and including a hydroxide ion conductive material and an electrically conductive material; an air electrode layer provided on the interface layer and including a catalyst layer made of a porous current collector and a layered double hydroxide (LDH) covering the surface of the porous current collector; a water-repellent porous layer covering the surface of the air electrode opposite to the hydroxide ion conductive separator; The cathode / separator assembly comprises:
2. The air electrode / separator assembly according to claim 1 , wherein the water-repellent porous material constituting the water-repellent porous layer contains a fluororesin material.
3. 3. The air electrode / separator assembly according to claim 2, wherein the fluororesin material is at least one selected from the group consisting of fully fluorinated resin, partially fluorinated resin, polyvinyl fluoride, and fluorinated resin copolymer.
4. 2. The air electrode / separator assembly according to claim 1, wherein the water-repellent porous layer is made of a porous material coated with water-repellent fine particles.
5. The cathode / separator assembly according to claim 4 , wherein the water-repellent fine particles include a fluororesin material.
6. 6. The air electrode / separator assembly according to claim 4, wherein the porous material is at least one selected from the group consisting of a polymer material, a metal mesh, and a carbon sheet.
7. The air electrode / separator assembly according to any one of claims 1 to 6, wherein the water-repellent porous layer has a thickness of 0.01 to 1 mm.
8. The air electrode / separator assembly according to any one of claims 1 to 7, wherein the water-repellent porous layer has a porosity of 30% or more.
9. 9. The air electrode / separator assembly according to claim 1, wherein the hydroxide ion conductive material contained in the interface layer is the same type of material as the hydroxide ion conductive material contained in the hydroxide ion conductive separator.
10. 10. The cathode / separator assembly of claim 9, wherein the hydroxide ion conducting material in the interfacial layer and the hydroxide ion conducting material in the hydroxide ion conducting separator are both LDH and / or LDH-like compounds.
11. The air electrode / separator assembly according to any one of claims 1 to 10, wherein the conductive material contained in the interface layer comprises a carbon material.
12. 12. The air electrode / separator assembly according to claim 11, wherein the carbon material is at least one selected from the group consisting of carbon black, graphite, carbon nanotubes, graphene, and reduced graphene oxide.
13. The air electrode / separator assembly according to any one of claims 1 to 12, wherein the catalyst layer has a porosity of 60% or more.
14. 14. The air electrode / separator assembly according to claim 1, wherein the LDH contained in the catalyst layer has a form of a plurality of LDH plate-like particles, and the plurality of LDH plate-like particles are bonded perpendicularly or obliquely to a surface of the porous current collector.
15. The cathode / separator assembly of claim 14 , wherein the LDH platelet particles are connected to each other in the catalyst layer.
16. 16. The air electrode / separator assembly according to claim 1, wherein the porous current collector is made of at least one material selected from the group consisting of carbon, nickel, stainless steel, and titanium.
17. The cathode / separator assembly according to any one of claims 1 to 16, wherein the porous current collector has a thickness of 0.1 to 1 mm.
18. 18. The cathode / separator assembly of claim 1, wherein the catalyst layer comprises a mixture including a hydroxide ion conducting material, an electrically conductive material, an organic polymer, and an cathode catalyst (provided that the hydroxide ion conducting material can be the same material as the cathode catalyst, and the electrically conductive material can be the same material as the cathode catalyst).
19. 19. The cathode / separator assembly of claim 1, wherein the hydroxide ion conducting separator is a layered double hydroxide (LDH) separator.
20. 20. The cathode / separator assembly of claim 19, wherein the LDH separator is composited with a porous substrate.
21. A battery comprising the air electrode / separator assembly according to any one of claims 1 to 20, a metal negative electrode, and an electrolyte, the electrolyte being isolated from the air electrode layer via the hydroxide ion conductive separator; A metal-air secondary battery in which, from the top, the metal negative electrode, the hydroxide ion conductive separator, the air cathode layer, and the water-repellent porous layer are stacked.
Citation Information
Patent Citations
Button type air-zinc battery
JP1997082372A
Air battery
JP2003151647A
Air electrode and metal air battery
JP2016071964A
Zinc-air secondary battery
WO2013073292A1
Air electrode and metal air battery
WO2015119041A1